2015
DOI: 10.7554/elife.05604
|View full text |Cite
|
Sign up to set email alerts
|

Natural genetic variation in Arabidopsis thaliana defense metabolism genes modulates field fitness

Abstract: Natural populations persist in complex environments, where biotic stressors, such as pathogen and insect communities, fluctuate temporally and spatially. These shifting biotic pressures generate heterogeneous selective forces that can maintain standing natural variation within a species. To directly test if genes containing causal variation for the Arabidopsis thaliana defensive compounds, glucosinolates (GSL) control field fitness and are therefore subject to natural selection, we conducted a multi-year field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
152
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(154 citation statements)
references
References 104 publications
1
152
0
1
Order By: Relevance
“…Consequently, plants have developed an arsenal of mechanisms to sense unfavorable situations and respond through a variety of signaling pathways that mediate a response. Inevitably, the launch of such responses requires resources and the plant often needs to make a trade-off that can affect yield (Todesco et al, 2010;Kerwin et al, 2015). In this study, our initial observations suggested that pdx3 mutants were activated for defense and suffered a yield penalty.…”
Section: Discussionmentioning
confidence: 72%
“…Consequently, plants have developed an arsenal of mechanisms to sense unfavorable situations and respond through a variety of signaling pathways that mediate a response. Inevitably, the launch of such responses requires resources and the plant often needs to make a trade-off that can affect yield (Todesco et al, 2010;Kerwin et al, 2015). In this study, our initial observations suggested that pdx3 mutants were activated for defense and suffered a yield penalty.…”
Section: Discussionmentioning
confidence: 72%
“…Recent studies have shown that the heterogeneous distribution of herbivores can shape plant defensive chemistry above ground [7][8][9]. Moreover, it was found that heterogeneity in herbivore communities maintains intraspecific variation in defence genes [10]. By contrast, the potential of belowground herbivores to shape chemical defences has remained elusive [21].…”
Section: Discussionmentioning
confidence: 99%
“…Insect herbivores, the most abundant and diverse plant consumers, have long been suspected to play an important role in this context [6]. Recent studies demonstrate that herbivore abundance can covary with the expression of plant defence metabolites [7], that the exclusion of phytophagous insects can lead to a relaxation of defences within a few generations [8] and that defence genes are under differential selection across environments [9,10]. Together, these studies show that the temporal and spatial variation in above-ground herbivore communities can shape plant defensive chemistry.…”
mentioning
confidence: 99%
“…If individuals that infect different hosts then mate and reshuffle their genetic diversity via meiotic or parasexual processes, they could potentially regenerate the population's initial mix of diversity while alleviating the linkage-drag effects of any selective or demographic bottlenecks in previous generations. This dynamic process of heterogeneous, fluctuating selection and reshuffling would allow genetic diversity to be maintained in the pathogen (Kerwin et al 2015;Turelli and Barton 2004). Given that generalist fungal pathogens with a broad host range are likely to encounter heterogeneous hosts and corresponding defenses from generation to generation, it is possible that fluctuating selection from these diverse host plant defense mechanisms may act to maintain phenotypic diversity within a generalist pathogen.…”
mentioning
confidence: 99%